Biological control: Helobdella triserialis lineata (Hirudinea:Glossiphonidae) over Biomphalaria straminea and Biomphalaria tenagophila (Mollusca: Planorbidae), in the laboratory - Guimarães, Carlos Tito; Souza, Cecília Pereira de; Consoli, Rotraut A.G.B.; Soares, Delza de Moura (Revista de Saúde Pública, 1984)
The predation of Helobdella triserialis lineata on specimens of Biomphalaria straminea and Biomphalaria tenagophila was observed in the laboratory. H. t. lineata was considered an efficient predator on newlyhatched snails, as well as on young and adult specimens of both planorbids. No predation on eggmasses was observed. A slight increased growth as well as a little reduction in oviposition was observed in snails kept together with the leeches.